Allozyme and DNA sequence data support speciation of Northern and Southern populations of silver catfish, Schilbe intermedius (Rüppel, 1832) - Bank, F. H. van der; Engelbrecht, G. D.; Sauer-Gürth, Hedwig; Wink, Michael; Mulder, P. F. S. (Comparative biochemistry and physiology. A, Molecular & integrative physiology, 1998)
Patterns of genetic variation in Schilbe intermedius were investigated due to morphological differences and taxonomic uncertainties regarding the Southern African schilbeids. A total of three populations, two Southern populations representing the former Eutropius depressirostris and a Northern population representing S. mystus, were electrophoretically analysed to determine the extent of genetic differentiation among these populations. The Northern and Southern populations were fixed for different alleles at the G3PDH-2 protein coding locus and allozyme differentiation between populations, using the 0.95 criterion, were also encountered at the PGDH-2 locus. Genetic distance values indicate greater genetic differentiation between the Northern and Southern populations compared to the two Southern populations. DNA sequence analysis of 900-1000 nucleotides of the cytochrome b gene revealed distances of 3.2-3.5% between the Schilbe/Eutropius complex. This finding, together with ingroup and outgroup analysis of evolutionary relationships, is congruent with the results from the electrophoretic analysis of the taxa. Sufficient differentiation exist between the Northern and Southern populations to regard them as distinct species.
Elektronische Reproduktion der Druck-Ausgabe 7. Januar 2000
Gesehen am 12.07.2023